Teror di Balik Layar: Cyberbulllying dan Krisis Identitas Digital Pelajar Muslim - Fika Wahyu Nurita; Arif Rahman (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Cyberbullying has become a severe issue in this digital age, especially among young people. According to a UNICEF survey (2020), around 45% of Indonesian teenagers aged 14–24 have experienced bullying via the internet. This phenomenon not only affects the mental health of victims but also damages their self-image. For Muslim students, cyberbullying can exacerbate the digital identity crisis due to the tension between religious values and the social pressures they face online. This study aims to analyze the concept of cyberbullying, its causes, psychological impacts, and its influence on the formation of Muslim students' self-identity. The methodology used is a literature review, analyzing relevant journals, books, and scientific articles. The results of the study show that cyberbullying comes in various forms, such as the spread of false information, threats, and online extortion, which can lead to depression, stress, and social isolation. Islamic spiritual values, such as compassion and brotherhood, can effectively build empathy and responsibility in the digital world. This article provides theoretical insights and practical solutions to reduce the impact of cyberbullying, while supporting the development of a positive digital identity for young Muslims.